Evaluation of resistance of Bt and non-Bt maize genotypes to Dalbulus maidis (Hemiptera: Cicadellidae) and associated mollicutes - Faria, Rodrigo Donizeti [UNESP]; Fanela, Thiago Luis Martins [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Lopes, João Roberto Spotti; Lourenção, André Luiz; Baldin, Edson Luiz Lopes [UNESP] (Springer Nature, 2022)
Corn is one of the main cereals grown in Brazil. However, attack of pest arthropods may compromise significantly crop yield. The corn leafhopper Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) is a vector of maize stunting pathogens, such as the mollicutes Spiroplasma kunkelli (corn stunt spiroplasma) and Candidatus Phytoplasma asteris (maize bushy stunt phytoplama). Resistant maize genotypes to the leafhopper and the associated mollicutes is a valuable strategy for reducing the dependence on synthetic insecticides for disease control. This study evaluated leafhopper infestation and incidence of mollicutes in 30 genotypes of Bt and non-Bt corn under field conditions in order to characterize possible resistance to both organisms. Two experiments were conducted in a randomized block design during the fall (2018) and the summer (2018/2019) seasons. The assessments of infestation by leafhopper nymphs and adults on plants were carried out every two weeks from the phenological stages V4 to V5 until VT-R1 for both seasons. The incidence of mollicutes in the genotypes was evaluated during the summer season by PCR analysis. There was no significant difference regarding the infestation by leafhopper adults on the genotypes studied in both seasons. However, genotypes 90XB06 Bt, SCS 156 Colorado, IAC 8046 and DKB 310 VTPRO3 were not infected by phytoplasma and spiroplasma, indicating their potential for resistance to these maize stunting pathogens. Our results can assist breeding programs focusing on maize genotypes resistant to the mollicutes transmitted by D. maidis.
Keywords: Corn stunting pathogens; Leafhopper vector; Maize resistance; Zea mays L